Implementasi Kebijakan Perlindungan Anak Korban Kekerasan Di Kabupaten Parigi Moutong - Lahaku, Jesika Olivia; Kurnia, Intam; Ferianto, Fiki (JPS: Journal of Publicness Studies, 2025)
Implementation of the policy of protection children victims of violence is still experiencing obstacles such as the limitations of the resources in this case the source of the budget and labor, then there is still a lack of understanding of the community in the importance of child protection From acts of violence, making the implementation of the policy of protection children not running optimally. This study aims to determine the obstacles that occur in the implementation of the policy of protection of women and children victims of violence in Parigi Moutong Regency. This study uses the theory of the implementation of van meter and van horn policies, namely there are 6 indicators of policy standards and objectives, resources, characteristics of implementing organizations, communication between related organizations, attitudes of implementers, social, economic and political environment. The results of this study indicate that the implementation of the policy of protection  children victims of violence in Parigi Moutong Regency is not optimal due to the limitations of resources, and social and economic environmental factors are also the biggest challenges inimplementation of this policy.